2022
DOI: 10.1155/2022/5971981
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Role of Serum Omentin and NGAL Levels in Egyptian Breast Cancer Patients

Abstract: Background. Breast cancer (BC) is globally the main cause of cancer-related deaths in women. Tumor biomarkers have significant role in diagnosis and predicting the prognosis and decide the specific therapy to each patient. Aim. In this study, we investigated whether omentin and NGAL levels were altered in patients with breast cancer and the relationship between these markers and their clinicopathological parameters. Subjects and Methods. This study included 120 patients with breast cancer and 30 healthy indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Improvement of the accuracy of biomarkers is a major goal for breast cancer early detection which has its impact on recurrence and prognosis. 18 This study aimed to evaluate resistin and RETN rs3219175 gene polymorphism and their relevance to diagnostic susceptibility, prognostic value, and genetic risk among Egyptian female patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of the accuracy of biomarkers is a major goal for breast cancer early detection which has its impact on recurrence and prognosis. 18 This study aimed to evaluate resistin and RETN rs3219175 gene polymorphism and their relevance to diagnostic susceptibility, prognostic value, and genetic risk among Egyptian female patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Abas et al [67] suggest that omentin-1 levels may complement the prognostic information available from classic prognostic factors such as tumor size, lymph node metastasis, and metastasis. In addition, the authors found no significant association between omentin-1 and prognostic factors such as hormone receptors and HER2 (human epidermal growth factor receptor 2) [67].…”
Section: Breast Cancermentioning
confidence: 99%